ANALISIS KETERLAKSANAAN SINTAKS GUIDED INQUIRY LEARNING BERBASIS PERFORMANCE ASSESSMENT PADA MATERI GETARAN DAN GELOMBANG - Adabiyah, Shoffyatul; An Nuril Maulida Fauziah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The implementation of an effective learning model is determined not only by planning but also by the execution of the learning process in the classroom. This study was conducted to describe the implementation of a guided inquiry learning model based on performance assessment for the topic of vibrations and waves. This study employed a descriptive quantitative approach with a sample of 28 eighth-grade students from Class VIII-A. Data were collected through learning implementation observation sheets evaluated by three observers as the learning process unfolded, and were subsequently analyzed in the form of percentages. The results indicated that the implementation of the learning process fell into the “very good” category, with a percentage of 91.67% for the vibrations topic and increased to 100% for the waves topic. All learning syntaxes could be implemented in accordance with the stages of guided inquiry learning, although in the initial session there was a time constraint on one of the sub-syntaxes. Overall, the optimal implementation indicates that the integration of performance assessment into the guided inquiry learning model is capable of supporting focused learning and actively involving students in every stage of the learning process